Utilization of palm oil biomass for treatment of low grade Malaysian iron ore - Hadi Puwanto, purwanto (2014)
As steel consumption increases, Malaysia’s steel production will increase, causing escalation in raw material consumption. Malaysia has no iron ore deposit, the low grade ore is an attractive alternative as a domestic iron resource. However, the use of low grade iron ore requires extra energy consumption. Development process for the utilization of waste biomass as an alternative energy source and utilization of low grade ore in iron-making is an attractive proposition. This paper discusses the possibility of using biomass waste from palm oil mill as energy source for the treatment of low grade Malaysian iron ore and its potential for steel industry toward green environment by lowering CO2 emission.